RANCANG BANGUN PERBANDINGAN LUAS BATERAI BERBAHAN ALUMINIUM MENGGUNAKAN ELEKTROLIT AIR LAUT BERSIRKULASI TERBUKA DENGAN SISTEM KONTROL DATA TERSIMPAN - Gilbert Mario Sembiring; Juan Evan Soaduon Tampubolon; Agus Dharma; I Gusti Agung Putu Raka Agung; I Made Mataram (Jurnal SPEKTRUM, 2025)
The utilization of renewable energy in Indonesia remains suboptimal, despite its substantial potential. One promising approach to harness this potential is through aluminum-air batteries using seawater as an electrolyte, offering greater safety and sustainability compared to conventional batteries. However, the performance of aluminum-air batteries can still be improved, particularly in terms of stabilizing the no-load voltage. This study aims to determine the voltage output generated by two battery design methods with identical electrode surface areas: one configuration using four cells measuring 5 × 5 × 0.2 cm arranged in series, and the other using a single cell measuring 10 × 10 × 0.2 cm. Both designs operate with an open circulation system. For testing, both battery configurations were monitored using an Arduino microcontroller as a voltage reader, which captured the voltage output from each battery. The voltage output from the aluminum-air batteries was read by the Arduino through the ADC pin and displayed in real time on a 16x2 I2C LCD screen, with the seawater circulation driven by a DC pump acting as the flow medium. The experimental results showed that the aluminum-air battery with four cells of 5 × 5 × 0.2 cm arranged in series achieved a maximum voltage increase of 255.7%, reaching 4.34 V, compared to the single-cell configuration of 10 × 10 × 0.2 cm, which produced only 1.22 V.